The Influence Of Company Size, Capital Structure, And Profitability On Company Value In Manufacturing Companies In The Logistics And Delivery Sector Listed On The IDX In 2019-2023 - Heppy Candra Berliana Dewi; Pristin Prima Sari; Alfiatul Maulida (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to test and analyze the effect of company size, capital structure, and profitability on company value in logistics and delivery companies listed on the IDX during the period 2019-2023. The variables tested in this study consist of company size, capital structure, and profitability as independent variables and company value as the dependent variable. This study uses a quantitative research type with sampling using the purposive sampling method, resulting in 9 companies that meet certain criteria, such as having complete financial reports. Hypothesis testing is carried out using multiple linear regression analysis to measure the direct effect. All analyses are carried out with the help of SPSS software version 25. The results of this study indicate that company size has a negative effect on company value, capital structure has a negative effect on company value, while profitability has a positive and significant effect on company value. The implications of this study are important for Logistics and Delivery companies in increasing company value by improving these factors.